2009
DOI: 10.1532/hsf98.20091051
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Architecture of Ventricular Myocardial Fibers in Ex Vivo Human Hearts

Abstract: The architecture of the ventricular myocardial fibers in the human heart conforms to the HVMB structural hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In our study, we found that there were damages in ascending and descending segments in heart with anterior wall infarction. According to Torrent's hypothesis, descending segment contraction is the main force for ventricle ejection and ascending segment contraction is the main force for ventricle filling during 'isovolumetric relaxation' phase of diastole [8]. Our results indicated greater damages in ascending segment than those in descending segment.…”
Section: Disscussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In our study, we found that there were damages in ascending and descending segments in heart with anterior wall infarction. According to Torrent's hypothesis, descending segment contraction is the main force for ventricle ejection and ascending segment contraction is the main force for ventricle filling during 'isovolumetric relaxation' phase of diastole [8]. Our results indicated greater damages in ascending segment than those in descending segment.…”
Section: Disscussionmentioning
confidence: 51%
“…This is) material basis of cardiac pumping function with high efficiency. Whatever causes damage in VMB will inevitably impair ejection and filling function [8]. …”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation